1991
DOI: 10.1002/jnr.490290408
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C stimulation enhances the process formation of adult oligodendrocytes and induces proliferation

Abstract: Oligodendrocytes (OL) isolated from adult pig brains regenerate their processes and form a network of fibers after 14-18 days in vitro (DIV). Stimulation of protein kinase C (Pk-C) by tumour promoters such as 12-O-tetradecanoylphorbol-13-acetate (TPA) produces at day 7 in vitro a similar network after only 20 hr. H-7, an inhibitor of Pk-C, as well as amiloride, which inhibits the subsequent Na+/H+ exchange, reversibly suppress this effect. Activation of the protein kinase A or calmodulin pathway do not result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
3
33
1
1
Order By: Relevance
“…Previous studies have shown that phorbol esters induce striking changes in oligodendrocyte morphology and act as mitogens for oligodendrocyte progenitors, probably by way of activating PKC [24,[46][47][48]. Inter estingly, some of these effects of phorbol esters are strik ingly similar to those of PDGF and FGF, two of the factors that profoundly influence oligodendrocyte devel opment.…”
Section: Resultsmentioning
confidence: 78%
“…Previous studies have shown that phorbol esters induce striking changes in oligodendrocyte morphology and act as mitogens for oligodendrocyte progenitors, probably by way of activating PKC [24,[46][47][48]. Inter estingly, some of these effects of phorbol esters are strik ingly similar to those of PDGF and FGF, two of the factors that profoundly influence oligodendrocyte devel opment.…”
Section: Resultsmentioning
confidence: 78%
“…3) (Yong et al, 1988;Althaus et al, 1991;Yong et al, 1991Yong et al, , 1994. The importance of PKC in this phorbol esterinduced extension has been confirmed by showing that inhibitors of PKC can block this event (Yong et al, 1988;Althaus et al, 1991;Yong et al, 1994). Investigators have since attempted to determine the signalling events following PKC activation in OL, and have found various downstream regulators of this kinase.…”
Section: Mature Olmentioning
confidence: 98%
“…They can also be cultured in the mature GalC stage from adult mammalian tissue; for instance, purified or enriched populations of mature OL have been isolated from cow, pig, sheep and human tissue (Szuchet et al, 1980;Kim et al, 1983;Smyrnis et al, 1986;Kim, 1990;Althaus et al, 1991;Kim and Kim, 1991;Stariha et al, 1997). The obvious advantage of primary OL cultures is that the cultured cells have direct in vivo counterparts, unlike artificial cell lines.…”
Section: The Primary Oligodendrocyte Culture Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The only relevant contaminating cells at the time in vitro, where most of our experiments were performed, were positively labeled for glial fibrillary acidic protein; their number comes to approximately 10% of the cell population (Althaus et al, 1991). Hence, we investigated whether pig astrocytes respond to NGF.…”
Section: Which Glial Cell Type Expresses Trka?mentioning
confidence: 99%